Modeling of Kinetics of Air Entrainment in Water Produced by Vertically Falling Water Flow - Adelė VAIDELIENĖ (Medžiagotyra, 2014)
This study analyzes the process of air entrainment in water caused by vertically falling water flow in the free water surface. The new kinetic model of air entrainment in water was developed. This model includes the process of air entrapment, as well as air removal, water sputtering and resorption. For the experimental part of this study a new method based on digital image processing was developed. Theoretical and experimental methods were used for determining air concentration and its distribution in water below the air-water interface. A new presented mathematical model of air entrainment process allows determining of air bubbles and water droplets concentrations distribution. The obtained theoretical and experimental results were in good agreement. DOI: http://dx.doi.org/10.5755/j01.ms.20.3.4871